The Political Communication of Independent Regulatory Agencies1. Issue 3 (28th July 2014) - Puppis, Manuel; Maggetti, Martino; Gilardi, Fabrizio; Biela, Jan; Papadopoulos, Yannis
Abstract: Since independent regulatory agencies (IRAs) became key actors in European regulatory governance in the 1990s, a significant share of policy‐making has been carried out by organizations that are neither democratically elected nor directly accountable to elected politicians. In this context, public communication plays an important role. On the one hand, regulatory agencies might try to use communication to raise their accountability and thereby to mitigate their democratic deficit. On the other hand, communication may be used with the intent to steer the behavior of the regulated industry when more coercive regulatory means are unfeasible or undesirable. However, empirical research focusing directly on how regulators communicate is virtually non‐existent. To fill this gap, this paper examines the public communication of IRAs in four countries (the United Kingdom, Germany, Ireland, and Switzerland) and three sectors (financial services, telecommunications, and broadcasting). The empirical analysis, based on qualitative interviews and a quantitative content analysis, indicates that the organization of the communication function follows a national pattern approach while a policy sector approach is helpful for understanding the use of communication as a soft tool of regulation.